2019
DOI: 10.20524/aog.2019.0417
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of ALBI, MELD, and Child-Pugh scores in prognosis of cirrhosis: is ALBI the new alternative?

Abstract: Background The existence of reliable prognostic indices is of paramount importance in the management of cirrhosis. Both the model for end-stage liver disease (MELD) score and the older Child-Pugh (CP) scores are widely used. The albumin-bilirubin (ALBI) score, initially used in hepatocellular carcinoma, has not been thoroughly investigated in cirrhosis. The aim of this study was to compare the prognostic accuracy of ALBI, MELD, MELD with sodium (MELD-Na), CP, and the corrected for creatinine CP scores in a gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 22 publications
3
21
0
1
Order By: Relevance
“…MELD XI and/or ALBI score (if the patient is on anticoagulants) are essential in screening for liver damage. [20][21][22][23] Additionally, the liver native T 1 values in our study showed good correlation with the two scores, suggesting that the liver native T 1 mapping may play an adjunct role in screening for FALD in adult Fontan patients. The prognostic significance of liver T 1 relaxometry requires further elucidation.…”
Section: Liver Native T 1 Values Serum Parameters and Meld/albi Scoresupporting
confidence: 67%
See 1 more Smart Citation
“…MELD XI and/or ALBI score (if the patient is on anticoagulants) are essential in screening for liver damage. [20][21][22][23] Additionally, the liver native T 1 values in our study showed good correlation with the two scores, suggesting that the liver native T 1 mapping may play an adjunct role in screening for FALD in adult Fontan patients. The prognostic significance of liver T 1 relaxometry requires further elucidation.…”
Section: Liver Native T 1 Values Serum Parameters and Meld/albi Scoresupporting
confidence: 67%
“…The MELD XI score = 11.76 × Ln (creatinine) + 5.11 × Ln (total bilirubin) + 9.44, and albumin-bilirubin (ALBI) score = [(log 10 bilirubin (μmol/L) × 0.66) + (albumin (g/L) × −0.085)], were determined as objective indicators of hepatic injury. 20,21 The MELD score is typically used to assess FALD; however, since adults Fontan patients are often prescribed with anticoagulants, we evaluated both the MELD XI, which excludes international normalized ratio (INR) and ALBI scores. 22,23 Twenty age-matched adults were enrolled as a control group.…”
Section: Methodsmentioning
confidence: 99%
“…[18][19][20] Fragaki, et al (2019), observaram que independentemente de etiologia, o escore o ALBI mostrou-se um preditor preciso e confiável na avaliação prognóstica de pacientes com cirrose descompensada, sendo igual ou superior a outros escores preditivos avaliados, como o MELD, CP e MELD-Na. 21 A adição da contagem de plaquetas ao escore ALBI, ocorre devido esse biomarcador estar relacionado ao efeito da hipertensão portal, que a principal causa de sangramento agudo das varizes esofágicas. Indicando que o poder prognóstico do ALBI seja maior em pacientes com disfunção hepática inicial, enquanto o PALBI tem melhor relação com a estratificação do risco de hipertensão portal.…”
Section: Discussionunclassified
“…Detection of splenomegaly, ascites, and portosystemic collaterals was also possible. Doppler US was done for the hepatic and portal veins, hepatic artery, and intra-abdominal portosystemic collaterals [10]. (4) Neurological assessment: we used neuropathy symptom and change (NSC) score to test and grade the presence of PN.…”
Section: Methodsmentioning
confidence: 99%